Permo–Triassic boundary carbon and mercury cycling linked to terrestrial ecosystem collapse - Jacopo Dal Corso (Nature Portfolio, 2020)
The environmental changes at the Permian–Triassic boundary are thought to have been caused primarily by volcanic eruptions. Here the authors develop a model to show that the loss of ecosystems on land and consequent massive terrestrial biomass oxidation triggered large biogeochemical changes in the oceans at the time of the marine mass extinction.